2014
DOI: 10.3126/ije.v3i2.10533
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of cadmium by Indian mustard (Brassica juncea L.) from cadmium contaminated soil: a phytoextraction study

Abstract: Cadmium is a toxic metal for living organisms and an environmental contaminant. Soils in many parts of the world are slightly too moderately contaminated by Cd due to long term use and disposal of Cd-contaminated wastes. Cost effective technologies are needed to remove cadmium from the contaminated sites. Soil phytoextraction is engineering based, low cost and socially accepted developing technology that uses plants to clean up contaminants in soils. This technology can be adopted as a remediation of cadmium f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Opposite tendencies in the Cd distribution in different parts of mustard plants to that presented in our studies were shown by Singh et al ( 2012b ), who claim that mustard is unsafe and not suitable for cultivation on Cd-contaminated soils. However, other researchers also recognized mustards, especially Indian mustard, as a high biomass crop species that accumulates substantial amounts of Cd (Salt et al 1995 ; Bhadkariya et al 2014 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Opposite tendencies in the Cd distribution in different parts of mustard plants to that presented in our studies were shown by Singh et al ( 2012b ), who claim that mustard is unsafe and not suitable for cultivation on Cd-contaminated soils. However, other researchers also recognized mustards, especially Indian mustard, as a high biomass crop species that accumulates substantial amounts of Cd (Salt et al 1995 ; Bhadkariya et al 2014 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…One good example of metal hyperaccumulators may be Zea mays (maize) (Wang et al 2007 ). Among the representatives of Brassicacae family, studies have widely investigated Brassica juncea , B. oleracea , B. rapa , Arabidopsis halleri , and A. thaliana (Nanda Kumar et al 1995 ; Jahangir et al 2008 ; Bhadkariya et al 2014 ; Kazemi-Dinan et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The infected fish were seen to suffer direct damage by Sclerocollum sp that included destruction of villi, hemorrhage, erosion of submucosa along parasites capsule and separation of submucosa from mucosa, among other observations. Bhadkariya et al (2014) also examine the area of bioremediation, focusing on the removal of Cadmium (Cd), a toxic material, from the soil. As the authors state, Cd is a heavy metal, and is considered a serious soil and environment pollutant due to its potential toxicity at low concentrations.…”
mentioning
confidence: 99%